Encyclopedia of Educational Philosophy and Theory 2017
DOI: 10.1007/978-981-287-588-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Modern Educational Aspirations

Abstract: Universal teaching is above all the universal verification of the similarity of what all the emancipated can do, all those who have decided to think of themselves as people just like everyone else. (Rancière 1991, p. 41

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…These studies demonstrated that religion – especially the influence of Protestant salvation themes on republicanism and cosmopolitanism – had substantially influenced the development of European and North American schooling, as well as of education, psychology and psychometrics as academic disciplines and political expertise. Challenging research narratives on the secularisation of modern schooling, they highlight the impact of religious thought on modern pedagogy, and argue that Protestant ideas have played an influential role in public life through modern pedagogised forms of religion (Buchardt, 2017). Therefore, religious narratives have equally shaped transnational discourses and policies of education as well as narratives of nationhood.…”
Section: Neoconservatism Populism Religion and Nationalismmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrated that religion – especially the influence of Protestant salvation themes on republicanism and cosmopolitanism – had substantially influenced the development of European and North American schooling, as well as of education, psychology and psychometrics as academic disciplines and political expertise. Challenging research narratives on the secularisation of modern schooling, they highlight the impact of religious thought on modern pedagogy, and argue that Protestant ideas have played an influential role in public life through modern pedagogised forms of religion (Buchardt, 2017). Therefore, religious narratives have equally shaped transnational discourses and policies of education as well as narratives of nationhood.…”
Section: Neoconservatism Populism Religion and Nationalismmentioning
confidence: 99%
“…Delving into the historical connections between religion, state and the politics of education, historiographic research contends that religion has fundamentally shaped the projects of nationbuilding through schooling as well as the languages of education circulating globally (Buchardt, 2017;Popkewitz, 2013;Tröhler, 2011). These studies demonstrated that religion -especially the influence of Protestant salvation themes on republicanism and cosmopolitanism -had substantially influenced the development of European and North American schooling, as well as of education, psychology and psychometrics as academic disciplines and political expertise.…”
Section: Neoconservatism Populism Religion and Nationalismmentioning
confidence: 99%
“…Az újabb oktatástörténeti kutatások kiemelik, hogy a vallásos világnézet és gondol kodás alapvető szerepet játszott az iskoláztatás révén megvalósuló nemzetépítési pro jektekben, és máig meghatározza az oktatáspolitika "nemzetközi nyelvezetét" (Buchardt 2016;Tröhler 2011). Elsősorban angolszász és nyugateurópai példákra hivatkozva kiemelik a protestáns üdvözüléstan meghatározó befolyását a modern iskoláztatás ki alakulásában, valamint az oktatástudományok és az oktatási tanácsadói szakértelem fejlődésében.…”
Section: áLlam éS Egyház Kapcsolatának Intézményi Vonatkozásaiunclassified
“…Elsősorban angolszász és nyugateurópai példákra hivatkozva kiemelik a protestáns üdvözüléstan meghatározó befolyását a modern iskoláztatás ki alakulásában, valamint az oktatástudományok és az oktatási tanácsadói szakértelem fejlődésében. A vallásos -elsősorban protestáns -gondolkodás mélyen átitatja a mo dern pedagógiai gondolkodást, és a pedagógián keresztül a közéletet is (Buchardt 2016;Vincent 2018).…”
Section: áLlam éS Egyház Kapcsolatának Intézményi Vonatkozásaiunclassified